1984
DOI: 10.1055/s-2008-1053061
|View full text |Cite
|
Sign up to set email alerts
|

Kombinierte Knochenmark- und Skelettszintigraphie bei ossären und myelogenen Erkrankungen

Abstract: In 87 patients with proved diagnosis and a normal or pathologic bone scan (BS) in addition a bone marrow scan (BMS) was performed using a 99mtechnetium-labelled microcolloid. The analysis of scintigraphic findings included those obtained by other investigations shows that in these selected patients a false normal or false positive interpretation would have been resulted in 18% performing the BS only. Both methods BS and BMS were capable of diagnosing the correct stage of disease in all patients. The results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
2

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
5
1
2
Order By: Relevance
“…Hence we cannot support the conclusions of Otsuka et al [32], who found BMS useful in distinguishing metastatic lesions from benign degenerative bone marrow changes in cases with suspected malignant bone involvement. Our findings are also at variance with those of Hotze et al [33], who recommended additional BMS in the case of equivocal BS to ascertain the diagnosis of metastases. Compared to BMS, MRI is much more specific as it can identify focal fatty conversion and differentiate this condition from metastatic marrow infiltration (Fig.…”
Section: Discussioncontrasting
confidence: 57%
“…Hence we cannot support the conclusions of Otsuka et al [32], who found BMS useful in distinguishing metastatic lesions from benign degenerative bone marrow changes in cases with suspected malignant bone involvement. Our findings are also at variance with those of Hotze et al [33], who recommended additional BMS in the case of equivocal BS to ascertain the diagnosis of metastases. Compared to BMS, MRI is much more specific as it can identify focal fatty conversion and differentiate this condition from metastatic marrow infiltration (Fig.…”
Section: Discussioncontrasting
confidence: 57%
“…After intravenous injection, 99mTc-nanocolloid is rapidly cleared from plasma and taken up by the RHS (Hotze et al 1984a). About 15%-20% of the injected dose is accumulated in the bone marrow by subendothelial macrophages (Hotze et al 1984a}, the rest being distributed mainly to the liver (70%) and spleen (10%) (ICRP 1989).…”
Section: Reticulo-histiocytic Systemmentioning
confidence: 99%
“…The mechanisms involved are microcolloid extravasation and -conceivably -phagocytosis by tissue macrophages or in vivo labelling of granulocytes infiltrating the inflammatory sites (Hotze et al 1984a;De Schrijver etal. The mechanisms involved are microcolloid extravasation and -conceivably -phagocytosis by tissue macrophages or in vivo labelling of granulocytes infiltrating the inflammatory sites (Hotze et al 1984a;De Schrijver etal.…”
Section: Inflammationmentioning
confidence: 99%
See 2 more Smart Citations